Long-range interactions of bismuth growth on monolayer epitaxial graphene at room temperature. (November 2015) - Chen, H.-H.; Su, S.H.; Chang, S.-L.; Cheng, B.-Y.; Chong, C.-W.; Huang, J.C.A.; Lin, M.-F.
Abstract: Long-range electronic interaction between Bismuth (Bi) adatoms on graphene formed on a 4H-SiC (0 0 0 1) substrate are clearly observed at room temperature ( T  = 300 K). Using scanning tunneling microscopy (STM) and density functional theory (DFT) calculations, we have demonstrated that such oscillatory interaction results mainly from the mediation of graphene Dirac-like electrons and the effect of the corrugated surface of SiC substrate. These two factors cause the observed oscillatory interaction with characteristic distribution distances and linear arrangements of Bi adatoms. The present study sheds light on understanding and controlling the nucleation of adatoms and subsequent growth of nanostructures on graphene surface.